Adjuvant role of macrophages in stem cell-induced cardiac repair in rats - Lim, Soo yeon; Cho, Dong Im; Jeong, Hye-yun; Kang, Hye-jin; Kim, Mi Ra; Cho, Meeyoung; Kim, Yong Sook; Ahn, Youngkeun (Experimental & molecular medicine, 2018)
Bone marrow-derived mesenchymal stem cells (BMMSCs) are used extensively for cardiac repair and interact with immune cells in the damaged heart. Macrophages are known to be modulated by stem cells, and we hypothesized that priming macrophages with BMMSCs would enhance their therapeutic efficacy. Rat bone marrow-derived macrophages (BMDMs) were stimulated by lipopolysaccharide (LPS) with or without coculture with rat BMCs. In the LPS-stimulated BMDMs, induction of the inflammatory marker iNOS was attenuated, and the anti-inflammatory marker Arg1 was markedly upregulated by coculture with BMMSCs. Myocardial infarction (MI) was induced in rats. One group was injected with BMMSCs, and a second group was injected with MIX (a mixture of BMMSCs and BMDMs after coculture). The reduction in cardiac fibrosis was greater in the MIX group than in the BMC group. Cardiac function was improved in the BMMSC group and was substantially improved in the MIX group. Angiogenesis was better in the MIX group, and anti-inflammatory macrophages were more abundant in the MIX group than in the BMMSC group. In the BMMSCs, interferon regulatory factor 5 (IRF5) was exclusively induced by coculture with macrophages. IRF5 knockdown in BMMSCs failed to suppress inflammatory marker induction in the macrophages. In this study, we demonstrated the successful application of BMDMs primed with BMMSCs as an adjuvant to cell therapy for cardiac repair. Heart attacks: mixed cell therapy for heart regeneration A tailored technique involving stem cells and anti-inflammatory immune cells shows promise for repairing heart tissue damage. Immune cells called anti-inflammatory macrophages are vital for healing of the heart following a heart attack. Youngkeun Ahn, Yong Sook Kim and co-workers at Chonnam National University Hospital in Gwangju, South Korea trialed a novel stem cell therapy on rats to improve cardiac repair. They took bone marrow-derived macrophages and stem cells from each rat and incubated the two cell types together to create individualized treatments. Following induced heart attacks, they injected one group of rats with both cell types, and another group with stem cells only. While heart function improved in both groups, the group treated with both cell types showed significant improvements with a greater reduction in cardiac fibrosis and increased the reparative activity of macrophages.